Estimación de los parámetros de ruptura del terremoto de Esmeraldas del 12 de diciembre de 1979, a partir de datos hidrográficos y simulación numérica de propagación de tsunamis. - Sanclemente, Eddy (2010)
The subduction zone of Northern Ecuador encounters four earthquakes of Mw> 7.5 in the last century. The area has been described as a segmented rupture zone with specific boundaries. We are interested at the 12th December1979 event. The seismic data available provided information, but most of the ruptured parameters are unknown or not well-constrained. A tide gauge record operated at Esmeraldas is available for the event. It is the purpose of this work to tentatively propose an accurate calibration of the rupture parameters for the 1979 event by using the tide gauge record and numerical simulations of the derived tsunami. The area is subject to large variations of the local bathymetry, with an underwater canyon surrounded by a shallow continental shelf, yielding strong spatial variation of the tsunami wave speed. Thus, numerical simulations require some high degree of precision. A temporary solution is proposed, that will be improved in the next months. Besides, it has been found that, unexpectedly, the northern part of the 1958 event area has been re-activated.